2016
DOI: 10.1016/j.actamat.2016.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of icosahedral short range order on diffusion in liquids: A study on Al-Zn-Cr alloys

Abstract: a b s t r a c tIt has been shown recently that minute additions of Cr in Al-Zn alloys refine the solidified grain structure and induce multiply-twinned grains which can only be explained if the icosahedral symmetry is considered (Kurtuldu et al., 2013). It has been suggested that Cr addition to Al-Zn alloys promotes the formation of icosahedral short-range order (ISRO) in the liquid, leading to the formation of icosahedral quasicrystals (iQC) acting then as a template for the nucleation of the fcc Al-phase. If… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…22,23 Indeed, in a liquid at high temperatures, the diffusion process is governed by uncorrelated binary atomic collisions and the diffusivities of the different components of the system should be essentially equal. However, in a glass-forming Zr-based alloy, Basuki et al 22 found that diffusivities and viscosity follow an Arrhenius-type law but a factor of 2 between Zr diffusion and the diffusion of smaller components like Co or Ni exists at high temperatures and becomes as large as four at the liquidus temperature.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Indeed, in a liquid at high temperatures, the diffusion process is governed by uncorrelated binary atomic collisions and the diffusivities of the different components of the system should be essentially equal. However, in a glass-forming Zr-based alloy, Basuki et al 22 found that diffusivities and viscosity follow an Arrhenius-type law but a factor of 2 between Zr diffusion and the diffusion of smaller components like Co or Ni exists at high temperatures and becomes as large as four at the liquidus temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the trinity Al-Zn-Cr alloys are very limited throughout the literature. Recently, Kurtuldu et al have investigated the effect of trace addition on the aging behavior of aluminum alloys containing Cr; moreover, the effect of Cr addition on Zn diffusions in molten of Al-Zn-Cr alloys [8,9]. It has been a subject of interest that minor and trace additives have a noticeable effect on these alloys, as far as structure and tensile properties are concerned [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been a subject of interest that minor and trace additives have a noticeable effect on these alloys, as far as structure and tensile properties are concerned [10]. In view of the outstanding corrosion and oxidation resistance, the strengthening and toughening of these alloys have been of recent concern [7][8][9][10][11]. Running experiments on the Al-Cr-Zn system at 600 • C, eleven three-phase regions had been identified [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is very interesting to notice that the minor and trace additives have a noticeable effect on these alloys as far as structure and tensile properties are concerned [10]. In view of the excellent corrosion and oxidation resistance, the strengthening and toughening of these alloys have been of recent interest [7][8][9][10][11]. Running experiments on the Al-Cr-Zn system at 600 °C, eleven three phase regions had been identified [12].…”
Section: Introductionmentioning
confidence: 99%
“…al. investigated the effect of trace additions on the aging behavior of aluminum alloys containing Cr and the effect of Cr addition on Zn diffusion in liquid Al-Zn-Cr alloys [8][9]. It is very interesting to notice that the minor and trace additives have a noticeable effect on these alloys as far as structure and tensile properties are concerned [10].…”
Section: Introductionmentioning
confidence: 99%